I think they think ... : overcoming social phobia - Rapee, Ronald M. (New York : Guilford Publications, 1998)
Portrays the effects of social phobia in sufferers' lives. Featured are interviews with three therapy patients with commentary by cognitive-behavioral therapists. Shows how cognitive behavioral therapy helps clients monitor their fears, challenge automatic and habitual thoughts, and expose themselves gradually to anxiety-provoking situations. The use of social situations and realistic thinking records are modeled. Also covered are the pros and cons of medication use, the role of group treatment and meditation, and coping with setbacks in recovery
Keywords: Phobic Disorders -- therapy; Cognitive Therapy -- methods; Social Isolation -- psychology; Social Adjustment